Difficulties faced by UTAR undergraduates during oral presentation in English as a form of assessment - Roshinie, Saravanan (2023)
At universities, there are students who fear oral presentation assessments. Hence, this research is conducted to identify the factors contributing to difficulties in speaking during oral presentations among UTAR undergraduates and to analyse the strategies to overcome the difficulties in speaking during oral presentations based on UTAR students’ perspectives. Survey questionnaires were sent via Google Form link to the participants in the Department of Public Relations. The findings show that the undergraduates agree that the contributing factors to difficulties in speaking during oral presentations are communication apprehension and test anxiety. To overcome these difficulties, the majority of the respondents agree that using techniques like having an outline, making useful notes, practicing, preparing good PowerPoint slides, and watching online videos of professional speakers can help the students present well. The findings of this research would be significant because students can be able to recognise their weaknesses during oral presentation assessments and find solutions to overcome their difficulties when speaking English. Besides that, lecturers can also modify their lesson plan by incorporating interesting activities that involve speaking and giving students more guidance on how to prepare for oral presentations. Along the way, this can help students reduce their speaking anxiety